Pathogenic potential of pigeonpea cyst nematode Heterodera cajani on blackgram - and A.K. JAIN, S.K. JAIN*, G.S. DAVE (Indian Phytopathology, 2002)
The pathogenic potential of pigeonpea cyst nematode Heterodera cajani was studied on blackgram in M.P. An initial inoculum of 2.5 x 103 larvae/2.5 kg soil caused significant reduction in emergence of first and second trifoliate leaves, flowers, fully grown green and dry pods alongwith seed yield and its morphological component characters. This reduction increased linearly with increase in initial inoculum levels. The reduction in yield was attributed to reduction in root system, pods, pod weight and seeds.